Spoiling the Stories The Rise of Israeli Women's Fiction - Merin, Tamar (Northwestern University Press, 2016)
In Spoiling the Stories, Tamar Merin presents the as yet untold story of the rise of prose by Israeli women, while further exploring and expanding the gendered models of literary influence in modern Hebrew literature. The theoretical idea upon which this book is based is that of intersexual dialogue, a term that refers to the various literary strategies employed by Israeli female fiction writers expressing their voice within a male-dominated and (still) inherently Oedipal literary tradition. Spoiling the Stories focuses on intersexual dialogue as it evolved in the first three decades after the establishment of the state of Israel in the works of Yehudit Hendel, Amalia Kahana Carmon, and Rachel Eytan. According to Merin, these three women writers were the most important in the history of modern Hebrew literature: each was a significant participant in the poetic development of her time.